Structural, optical, and electrical properties of proton intercalation H+/Na+ phases in nanostructured titanates induced by pH during hydrothermal synthesis. (December 2022) - Amy, Lucia; Favre, Sofia; Faccio, Ricardo
Abstract: In search of a promising alternative to manufacture anodes for sodium-ion batteries, a study of the pH variation during hydrothermal synthesis of nanostructures of sodium titanate is presented. In particular, structural, optical and electrical properties of these materials are assessed when varying the pH for two different synthesis conditions. A mixture of phases was found, in agreement with ( N a, H ) 2 T i 3 O 7 ⋅ n H 2 O, and its cause is attributed to the proton( H + )/sodium( N a + ) exchange and the intercalation of structural water. Also, changes in the morphology of the structural phases were observed, for example the phase with lower interlaminal distance appears to be nanorods, instead of nanotubes. The relative weight between phases and the direct band gap can be tuned by controlling synthesis conditions, in particular pH conditions. An enhancement of new processes in the electrical response and the suppression or enhancement of some defect due to the mixture of phase is also discussed. Additionally, the changes in electrical properties over a possible operation temperature range of a potential device, between −30 °C and 50 °C is reported. It was found that the changes in impedance in the proposed temperature range are of the order of 25 % of the modulus. This work shows how the final N a + content in the sample alters its optical and electrical properties, which are determinant in its performance as an anode. Graphical abstract: Highlights: Effect of pH during the synthesis of sodium titanate nanostructure. Mixture of phases concordant with (Na, H)2 Ti3 O7 .nH2 O. Mixture of phases regulates optical and electrical properties. Direct Band gap could be tuned with pH during synthesis. Study of the electrical impedance in the operation temperature range.